LEADERSHIP IN TECHNICAL AND VOCATIONAL EDUCATION - Hashim, Jamaluddin; Mohamad, Baharom; Md. Jidi, Kamarolzaman; Zainal Abidin, Ramlan; Junoh, Hussein (Journal of Technical Education and Training, 2010)
Good leadership in the lifelong learning of technical and vocational education exists when the leaders are able to perform either one or combination of transformational leadership characteristics, even though, less emphasis on these characteristics can affect job satisfaction of his or her subordinates. This study investigated transformational of Heads of Departments at the Polytechnics with regards to the job satisfaction of the lecturers. Respondents of this study are made up of 365 lecturers randomly selected from the polytechnics in Malaysia. Survey instrument had been used. Data obtained is analyzed using means and Pearson correlation methods. Results of the study show the elements of intellectual stimulation (mean = 3.18), increasing influence (mean = 3.17), providing reasoning as individuals (mean = 3.08) and inspirational motivation (mean = 3.04) are high; as well as a high job satisfaction level (mean = 3.16). The Pearson correlation analysis indicates that all four transformational leadership in the life long learning characteristics practiced by Heads of Departments at the Polytechnics have strong and significant correlations with the job satisfaction of the lecturers. As a conclusion, Heads of Departments at the Polytechnics is practicing transformational leadership in the life long learning characteristics in the administration of departments.